Pengaruh Struktur Modal, Pertumbuhan Laba, dan Komite Audit Terhadap Kualitas Laba Pada Perusahaan Industri Barang Konsumsi Yang Terdaftar Di BEI Tahun 2017-2020 - Tri Yuli Astuti; Sully Kemala Octisari; Ginanjar Adi Nugraha (FEB UNWIKU PURWOKERTO, 2022)
This study aims to determine the effect of capital structure, earnings growth, and audit committee on earnings quality in consumer goods industrial companies listed on the Indonesian stock exchange in 2017-2020. The population used in this study is the consumer goods industrial companies listed on the BEI as many as 52 companies. The sampling technique in this study used a purposive sampling technique which obtained 26 consumer goods industrial companies listed on the IDX in 2017-2020. The analytical method used is panel data regression with the help of STATA statistics. The results of the analysis show that capital structure and profit growth have a significant positive effect on earnings quality in consumer goods industrial companies listed on the IDX in 2017-2020. However, the audit committee has no significant negative effect on earnings quality in consumer goods industrial companies listed on the IDX in 2017-2020.